2009
DOI: 10.1007/s11104-009-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic lift: soil processes and transpiration in the Mediterranean leguminous shrub Retama sphaerocarpa (L.) Boiss

Abstract: Hydraulic lift (HL) is the process by which plants can passively transfer water from deep, moist soil layers to shallow, dry soil layers. Although it has attracted recent research interest, a mechanistic understanding and its implications for ecosystem functioning are still lacking. Here we describe HL seasonal patterns in a semi-arid shrub species and its influence on plant water dynamics. We measured soil water availability and plant water status over the course of 1 year. Soil water potential in the rhizosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…We found that the quantity of water released though HL into shallow soil layers was minimal when these layers were very dry (-4 to -6 MPa), whereas more water could be redistributed into moderately dry upper soil layers (-1 MPa), even though the soil water potential gradient was smaller. Similar results were also found under R. sphaerocarpa shrubs in the same area by Prieto et al (2010). An explanation could be the nonlinear relationship between soil water potential and soil water content, which in our model resulted in decreased HL magnitude at low water potentials (see Figs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that the quantity of water released though HL into shallow soil layers was minimal when these layers were very dry (-4 to -6 MPa), whereas more water could be redistributed into moderately dry upper soil layers (-1 MPa), even though the soil water potential gradient was smaller. Similar results were also found under R. sphaerocarpa shrubs in the same area by Prieto et al (2010). An explanation could be the nonlinear relationship between soil water potential and soil water content, which in our model resulted in decreased HL magnitude at low water potentials (see Figs.…”
Section: Discussionsupporting
confidence: 87%
“…4,5). The large gradients in soil water potential present during drought resulted in the release of smaller amounts of water into the top soil layers under R. sphaerocarpa (Prieto et al 2010). Nonetheless, factors such as a decrease in root hydraulic conductivity or a loss of root-soil contact can also explain the sharp decrease in HL rates in very dry soils (Domec et al 2004;Warren et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This increases the aboveground biomass of the herbaceous understory (Moro et al 1997;Rivest et al 2011a). Prieto et al (2010) also provided evidence to show that Retama is able to hydraulically lift and release water from deep to shallow soil layers during pronounced dry periods. However, when estimating pasture production at plot scale in this study, no significant response to the presence of Retama was observed.…”
Section: Shrub Browse Productionmentioning
confidence: 93%
“…However, a study of two species (beech and spruce) in the Tharandt forest, Germany showed that soil water shortage led to a significant reduction in the transpiration rate of spruce, but not of beech (Schwärzel et al, 2009). Root distribution reduces the influence of soil water drought on plant transpiration, especially in deep-rooted species that have the ability to access and utilize deep soil water and groundwater overcoming soil drought without any significant changes in transpiration (Prieto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%